Adipose tissue growth and development: the modulating role of ambient temperature. Issue 1 (January 2021) - Symonds, Michael E; Pope, Mark; Bloor, Ian; Law, James; Alagal, Reham; Budge, Helen
Abstract : Adipose tissue is usually laid down in small amounts in the foetus and is characterised as possessing small amounts of the brown adipose tissue-specific mitochondrial uncoupling protein (UCP)1. In adults, a primary factor determining the abundance and function of UCP1 is ambient temperature. Cold exposure causes activation and the rapid generation of heat through the free flow of protons across the mitochondria with no requirement to convert ADP to ATP. In rodents, housing at an ambient temperature below thermoneutrality promotes the appearance of beige like adipocytes. These arise as discrete regions of UCP1 containing cells in white fat depots. There is increasing evidence to show that to gain credible translational results on brown and beige fat function in rodent models that they should be housed at thermoneutrality. This not only reflects the type of environment in which humans spend a majority of their time, but is in accord with the rise of global temperature caused by industrialisation and the uncontrolled burning of fossil fuels. There is now good evidence in adult humans, that stimulating brown fat can improve glucose homeostasis which can be achieved either by nutritional or pharmacological interventions. The challenge, therefore, is to establish credible developmental models in animals maintained at thermoneutrality which will elucidate the true impact of nutrition. The primary focus should fall specifically on the components of breast milk and how these modulate long term effects on brown or beige fat development and function.